Implosion And Ultrasonic Cavitation At Low Frequency Waves Against Carbon Pore Morphology - Toana, Musfirah Cahya Fajrah (Gravitasi, 2014)
Abstract Havestudiedthe effect oflow-frequencyultrasonicwave technologythat producesanddistributes47kHzimplosionof cavitationon the morphology ofthe carbonpore formation. Pore formationis donebyvariationof ultrasonictimefor 10 hoursand60 hours, at a temperature of900oC, 1000oCand1200oC. The morphology ofthe poreformationfor 10hoursresulted inporemorphologywith a size of200nmto1000oCand1200oCtemperaturecoveragebutdoes notoccurin eachporeuniformity ofthe grainsize. Pore formationfor 60hoursresulted inporesbutto900oCtemperaturecoveragedoes notoccurporeuniformity, in contrast tothe temperature of1000oCand1200oCcoverageoccursuniformity ofthe porebyporesize of185nm. Keywords: ultrasonic, cavitation, implosionandcarbonpore